Morphological description and DNA barcoding of Hydrobaenus majus sp. nov. (Diptera: Chironomidae: Orthocladiinae) from the Russian Far East - Makarchenko, Eugenyi A.; Makarchenko, Marina A. (Zootaxa, 2015)
Illustrated descriptions of adult male, pupa and fourth instar larva, as well as DNA barcoding, of Hydrobaenus majus sp. nov. in comparison with the close related species H. sikhotealinensis Makarchenko et Makarchenko from the Russian Far East are provided. The species-specificity of H. majus sp. nov. COI sequences is analyzed and the sequences are presented as diagnostic characters—molecular markers of H. majus and H. sikhotealinensis.